THE INFLUENCE OF FORMATIVE ASSESSMENT ON IMPROVING STUDENTS’ ENGLISH SPEAKING SKILLS - Septia Mardella; Zuhri Efendi (Nusantara Hasana Journal, 2025)
In this study, the effects of formative assessment on students' English language proficiency—specifically, EFL/ESL learners—are examined. Formative assessment is a crucial component of the classroom learning process and has been shown to improve students' academic performance and engagement. The impact of formative assessment on raising students' English competence at MTsN 1 Susoh was examined using a descriptive qualitative research methodology. The English teachers at MTsN 1 Susoh are the study's participants. Additionally, the researcher chooses two teachers who employ formative assessment to gauge their pupils' speaking proficiency using a purposive selection technique. Data were acquired through observation and interview procedures. This study highlights how crucial it is to establish an engaging classroom where students can freely express their ideas and work together with their peers. Students are more motivated to learn English thanks to this method, which also promotes participation. According to the results, formative assessment can greatly enhance students' speaking abilities if it is used properly. This is because it encourages students to actively participate in their evaluation process by establishing criteria and doing self-evaluation. Despite its advantages, formative evaluation is still difficult to apply successfully due to problems including packed classrooms and time management. In the end, this study promotes the use of formative assessment methods in English language instruction to enhance students' speaking proficiency and overall educational experience.